International legal protection of children from the crime of abduction - Boudjelal, Soumia (Journal of Human Sciences, 2025)
The crime of abducting children from old crimes has escalated and has spread significantly in recent times. And that is whey it has been classified as one of the most important crimes against children and the most serious of all, especially because it has become linked to organized crime, to protect children from them, States have strengthened and intensified their efforts at the international level to combat and address them by concluding and establishing numerous international conventions and protocols, all of which call for the protection of children and the preservation of their rights. It stipulates a number of legal principles and rules by which the child is accorded the utmost care for his or her rights and combating the various crimes against him or her, in particular the crime of abduction.